Pragmatic meaning of advertising discourse in Medan local newspaper - Desri Wiana (Politeknik Negeri Bali, 2019)
Pragmatics is the study of the aspects of meaning in which the speaker expressed or communicated and a listener interpreted it. In other words, pragmatics covered the study of language sense which is communicated by the language user. Meanings or language senses that is expressed by the language users implies beyond the meanings that are expressed in the writings. This paper focused on the advertising discourses that exposed in Medan, North Sumatera local newspaper; that is Analisa. The aim of this paper is to explore the pragmatics meaning of advertising discourses in Analisa newspaper, in which applied the theory of implicature, presupposition, coherence, and background analysis. The data collected were totally 120 advertising discourses. The technique of analysis data that were applied is descriptive analysis. The findings are revealed that Analisa newspaper consisted of 14 pragmatics meaning. Offering products are the most dominantly pragmatic meanings expressed in the newspaper. This shows that the purpose of commercial ads in the local newspaper tends to offer products for selling to the community and to market as well.